Comparative anatomical and micromorphological study of some Rumex species (Polygonaceae) - Keshavarzi, Maryam; Ebrahimi, Farzaneh; Mosaferi, Samaneh (Acta Biologica Szegediensis, 2018)
Rumex (Polygonaceae) is a large genus of annual, biennial and perennial species in temperate regions of the world. In Iran it is represented by 23 species and some hybrids classified in three subgenera. The species identification is difficult due to the importance of fruit features in species separation despite the fact, that plants lose their flower and some other features while bearing fruits. Providing the individuals with the proper set of diagnostic features is very difficult. There are inadequate anatomical studies of Rumex. The present study reports the first detailed stem anatomy and epidermis micromorphology of 6 species of Rumex in Iran. Main aims of this study were to find the diagnostic value of the adopted features. Cross sections were made by hand and double colored. Dorsal and ventral leaf epidermises were studied by Scanning Electron Microscopy (SEM). Results of stem anatomical study showed that collateral vascular bundle is only present in R. chalepensis and oxalate calcium druse crystals were only absent in R. elbrusensis. The micro-morphological study of epidermis showed that all species studied had anisocytic stomata type, but there were differences in the epidermis and stomata cell size. Species relationships based on the results have been discussed.